If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2x+26=2
We move all terms to the left:
-2x+26-(2)=0
We add all the numbers together, and all the variables
-2x+24=0
We move all terms containing x to the left, all other terms to the right
-2x=-24
x=-24/-2
x=+12
| -9/5+8/5=-1/2x+3 | | 7y-27=2(y+9 | | 5u-25=2(u-5) | | x2+14x+49=9 | | 0.5x-3=13 | | 2x2+10=60 | | x+2x/3+x/2+x/7=33 | | x+15=1/2(30+(9x-42)) | | 33=x=58 | | 3(-x+9)=8-6x | | 3x+2x+5=8x-13 | | 20=6y+8 | | x+(x+5)+2(x+5)=35 | | 4x+(3x+1)=6-2(x-1) | | 6+-3m=15 | | 30=2(u+6)-5 | | 7x+6=x+6 | | -6=-8w+5(w-3) | | 10x+4=8x+24 | | 4a=4-20 | | 10x5=20-20x | | w+14=√256 | | 4x^-56x+196=0 | | 6.5=8.9-0.8x | | 164°-x=x+60° | | -6=-8w+5(w-3 | | 4(2x+7)-7=13 | | 2=3*2x | | 4x+5x-8=10 | | -5t=8-5 | | 5u/4-24/4=0 | | -8(n+8)=-112 |